PAGET'S DISEASE: CURRENT TREATMENT MODALITIES - Yulia Leonidovna Korsakova (Современная ревматология)
Paget's disease is a chronic local bone disease included into a group of metabolic osteopathies in which rearrangement foci emerge in one or several bones. The disease is characterized by the appearance of ostealgia, skeletal deformity, or, for example, hearing loss occurring with skull lesion or hip or knee arthrosis and, less frequently, sarcoma or giant cell tumor. There is evidence that bisphosphonates may control the activity of Paget's disease as they inhibit the function of osteoclasts. The use of these drugs reduces the intensity of osteoalgia and the level of biochemical markers for bone resorption and osteogenesis and can decelerate or reverse the early osteolytic phase of the disease. It is promising to use of zolendronic acid (Aclasta, 5 mg), a new heterocyclic amino-containing bisphosphonate that has a significantly higher efficacy than previously used antiresorptive agents.